2015
DOI: 10.7243/2052-6180-3-5
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics in personal care products

Abstract: In recent years, probiotics have attained popularity among consumers worldwide as a natural approach to maintain or restore human health. As a billion dollar industry, many products are already available in the market place with even more potential candidates in development. Knowledge gained from the Human Microbiome Project supports the utility of probiotics to achieve a balanced microbial community and potentially reduce or alleviate certain disorders. Most of the research studies and commercial probiotic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…Today a large number of probiotics-based cosmetics are used in different forms and numerous products are available in the market. Cosmetics refer to substance or products indented to be rubbed, poured, sprinkled or sprayed on, introduced into, or otherwise applied to the human body or any part thereof for cleansing, beautifying, promoting attractiveness or altering appearance (Huang & Tang, 2015). Microbiome such as Staphylococcus spp.…”
Section: Probiotics Application In Cosmeticsmentioning
confidence: 99%
“…Today a large number of probiotics-based cosmetics are used in different forms and numerous products are available in the market. Cosmetics refer to substance or products indented to be rubbed, poured, sprinkled or sprayed on, introduced into, or otherwise applied to the human body or any part thereof for cleansing, beautifying, promoting attractiveness or altering appearance (Huang & Tang, 2015). Microbiome such as Staphylococcus spp.…”
Section: Probiotics Application In Cosmeticsmentioning
confidence: 99%
“…Especially in case of inflammatory or autoimmune disorders, such as atopic dermatitis (AD) there is now clear evidence that they are associated with shifts in the resident microbiota from a healthy to a diseased state and that they can be viewed as dysbiotic host-microbial states (Belkaid and Segre, 2014). In cases of psoriasis, where dysbiosis is associated with skin inflammation, oral probiotics has been suggested as a means to restore the resident microbes, that are diminished when the disorder is present (Huang and Tang, 2015). It was reported that pattern recognition receptors, such as Toll-like receptor (TLR) 2 of the innate immune system, are triggered by commensal S. epidermidis (Stevens et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, AD is a common chronic or relapsing inflammatory disease of the skin that often precedes asthma and allergic disorders (Boguniewicz and Leung 2011). AD is prevalent among children and often resolves in adolescence or adulthood (Huang and Tang 2015). A dysfunctional skin barrier and an imbalanced immune system (Boguniewicz and Leung 2011) are two of several causes of these skin disorders.…”
Section: Probiotics and Prebiotics Effects On Skin Healthmentioning
confidence: 99%
“…This condition stimulates the progress of infection and complications (Rahman et al 2011). Patients with AD usually acquire cutaneous infections by Staphylococcus aureus, the main colonizing organism (Huang and Tang 2015).…”
Section: Probiotics and Prebiotics Effects On Skin Healthmentioning
confidence: 99%